Implementation of Flutter Framework in Frontend Development of Android-Based Audio Scheduling Application - Jamila , Andi Cleopatra Maryam; Prasasti , Anggunmeka Luhur; Fikri , Rifqi Muhammad (eProceedings of Engineering, 2025)
Abstrak — Flutter is an open-source framework developedby Google to support cross-platform mobile applicationinterface development. This study implements Flutter in thefrontend development of an Android-based audio schedulingapplication designed to improve information delivery in earlychildhood education environments. The case study wasconducted at TK IT Little Moslem, where manual bells andspeakers were still used, resulting in inefficient communication.The developed application, named SoundNest, allows teachersto schedule audio playback (bells, music, and Qur’anicrecitations), control volume, and deliver announcementsthrough a user-friendly interface. Flutter was used to buildinteractive layouts using widgets such as ListView, Switch, andTabBar, while Firebase Realtime Database handled real-timedata storage and synchronization. Testing was conducted usingwhite-box, black-box, and User Acceptance Testing (UAT)methods, with 13 teachers participating as respondents. TheUAT yielded an average score of 56.69 out of 60, and theCronbach’s Alpha reliability score was 0.947, indicatingexcellent internal consistency. The results confirm that theapplication is efficient, responsive, and easy to use. Thus, Flutterproves effective for building dynamic and educational Androidinterfaces and serves as a functional solution to improvecommunication at TK IT Little Moslem.Keywords — flutter, frontend, android, audio scheduling,firebase, user interface.